Heat-resistant crosslinked polyolefin foam and its manufacturing method

JP7645445B2Active Publication Date: 2025-03-14SANWA KAKO CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020156901
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-18
Publication Date
2025-03-14
Estimated Expiration
2040-09-18

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、発泡に先立つ混練工程を比較的低温で行うことができるので、融点が低く耐熱性の高くない樹脂を主原料とする製品の製造ラインをそのまま利用して耐熱性を有する架橋ポリオレフィン発泡体を製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645445000003
    Figure 0007645445000003
  • Figure 0007645445000004
    Figure 0007645445000004
  • Figure 0007645445000001
    Figure 0007645445000001
Patent Text Reader

Abstract

To provide a method for producing a heat-resistant crosslinked polyolefin foam, the method enabling a kneading step to be performed prior to foaming at comparatively low temperatures so that a production line of a product containing a resin not having heat resistance as a main raw material can be used as it is.SOLUTION: A method for producing a heat-resistant crosslinked polyolefin foam includes the steps of: adding powder of an additive formed from a resin having a melting point of 120°C or higher into a polyolefin resin having a melting point of lower than 120°C as a main raw material thereby producing a pre-foaming mixture; adding a foaming agent and a crosslinking agent to the pre-foaming mixture; kneading the powder at a temperature higher than 120°C and lower than a melting point of the additive, and dispersing the powder in the pre-foaming mixture; and heating the pre-foaming mixture to a temperature enabling the additive to be melted thereby foaming the pre-foaming mixture.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat-resistant crosslinked polyolefin foam and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art It is widely practiced to prepare a foam by adding a foaming agent and a crosslinking agent to a polyolefin resin, kneading the resulting mixture to obtain a crosslinkable foamable composition, and then heating the composition to cause it to foam.

[0003] Foams whose main ingredient is a resin with a low melting point and low heat resistance, such as low-density polyethylene (LDPE), shrink significantly when heat is applied.

[0004] In order to prevent the foam from shrinking at high temperatures, it is possible to use a more heat-resistant resin, such as high-density polyethylene (HDPE), as the raw material. However, this would change the texture of the foam and require changes to the manufacturing process.

[0005] Therefore, there is a demand for a method for producing a crosslinked polyolefin foam that has little shrinkage at high temperatures while using a resin that is not highly heat-resistant as a main raw material. One method is known in which pellets are obtained by fibrillating polybutylene terephthalate in a polyethylene resin, and a foaming agent and a crosslinking agent are added to and kneaded with the pellets to cause foaming (see, for example, Patent Document 1).

[0006] However, in the method described in Patent Document 1, when obtaining pellets in which polybutylene terephthalate is fibrillated in polyethylene resin, kneading at a high temperature of 200°C is required, which has the problem that it is difficult to directly use a production line for products whose main raw material is a resin with a low melting point and low heat resistance.

[0007] Another possible method is to knead a resin having a high melting point and high heat resistance with a resin having a low melting point and low heat resistance in order to impart heat resistance. However, when a resin having a high melting point is melted and kneaded, foaming reactions and crosslinking reactions proceed during the kneading process, making it difficult to form a foam having a good shape. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 4605364 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to enable the production of a heat-resistant crosslinked polyolefin foam to be made possible by utilizing, as is, a production line for a product whose main raw material is a resin having a low melting point and low heat resistance. [Means for solving the problem]

[0010] The method for producing a heat-resistant cross-linked polyolefin foam according to the invention of claim 1 includes the steps of: adding a powder of an additive having an average particle size of 10 μm to 20 μm, the powder being made of a resin having a melting point of 120° C. or higher, to a polyolefin resin having a melting point of less than 120° C. as a main raw material, to produce a pre-foaming mixture; adding a foaming agent and a cross-linking agent to the pre-foaming mixture; The melting point of the polyolefin resin is less than 120°C. The method also includes a step of kneading the pre-foaming mixture at a temperature lower than the melting point of the additive to disperse the powder of the additive in the pre-foaming mixture, and a step of heating the pre-foaming mixture to a temperature at which the additive can be melted to foam the mixture.

[0011] According to such a production method, the additive powder is dispersed by kneading at a temperature higher than the melting point of the polyolefin resin, which is the main raw material, and lower than the melting point of the additive, and then the additive powder is heated to a temperature at which the additive can melt and expanded, whereby the additive powder melts and fibrillates during the expansion process, thereby imparting heat resistance to the crosslinked polyolefin foam. Therefore, since the kneading process can be performed at a relatively low temperature corresponding to the melting point of the polyolefin resin, which is the main raw material, the heat-resistant crosslinked polyolefin foam can be produced using the equipment corresponding to the polyolefin resin, which is the main raw material, as it is.

[0012] In the present invention, the term "temperature at which an additive can melt" refers to a temperature equal to or higher than the melting point of the additive, or a temperature that is lower than the melting point but is 10° C. or less different from the melting point. During the foaming process, heat is generated when the foaming agent and the main raw material react, so the temperature of the raw material during the foaming process is about 5 to 10° C. higher than the heating temperature. Therefore, even if the heating temperature is lower than the melting point, it is possible to melt the powder of the additive during the foaming process as long as the difference from the melting point is 10° C. or less.

[0013] Examples of polyolefin resins having a low melting point that can be used in such a production method include low-density polyethylene and ethylene-vinyl acetate copolymers.

[0014] Examples of additive powder components used in such manufacturing processes include high density polyethylene or polypropylene.

[0015] The heat-resistant crosslinked polyolefin foam according to the invention of claim 4 is formed from a polyolefin resin having a melting point of less than 120°C as a main raw material and a resin having a melting point of 120°C or more. Average particle size is 10μm~20μm This includes additives that have melted and fibrillated. Effect of the Invention

[0016] According to the present invention, since the kneading step prior to foaming can be carried out at a relatively low temperature, a heat-resistant crosslinked polyolefin foam can be produced by directly utilizing a production line for a product whose main raw material is a resin having a low melting point and low heat resistance. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a diagram showing the FT-IR spectrum intensity of a heat-resistant crosslinked polyolefin foam according to one embodiment of the present invention before a foaming process. [Diagram 2] FIG. 4 is a diagram showing the FT-IR spectrum intensity of the heat-resistant crosslinked polyolefin foam according to the embodiment after the foaming process. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described. In this embodiment, a polyolefin-based foam having high heat resistance is produced by adding an additive formed of a resin having a melting point of 120°C or higher, specifically, a powder of polypropylene or high-density polyethylene, to a polyolefin resin having a melting point of less than 120°C, which is the main raw material. This foam is produced by adding a blowing agent, a crosslinking agent, and a powder of polypropylene or high-density polyethylene to the polyolefin resin and kneading them to obtain a crosslinkable foamable composition, and then heating the composition to foam it.

[0019] Specific examples of polyolefin resins that are the main raw material for foams include those with melting points of less than 120° C., such as low-density polyethylene (LDPE) and ethylene-vinyl acetate copolymer (EVA).

[0020] Specific examples of the foaming material include organic chemical foams such as azo compounds such as azodicarbonamide and barium azodicarboxylate, nitroso compounds such as dinitrosopentamethylenetetramine and trinitrotrimethyltriamine, hydrazide compounds such as p,p'-oxybisbenzenesulfonylhydrazide, and sulfonylsemicarbazide compounds such as p,p'-oxybisbenzenesulfonylsemicarbazide and toluenesulfonylsemicarbazide. However, inorganic foaming agents such as sodium bicarbonate can also be used.

[0021] The crosslinking agent is an organic peroxide that has a decomposition temperature in the polyolefin resin that is at least equal to or higher than the flow temperature of the polyolefin resin, and is a radical generator that is decomposed by heating to generate free radicals and form crosslinks between or within the molecules. Specific examples of the crosslinking agent include dicumyl peroxide, n-butyl 4,4-bis(t-butylperoxy)valerate, and 1,1-ditertiarybutylperoxide. Examples of organic peroxides include 1,1-ditertiary butylperoxy-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-ditertiary butylperoxyhexane, 2,5-dimethyl-2,5-ditertiary butylperoxyhexyne, α,α-ditertiary butylperoxyisopropylbenzene, tertiary butyl peroxyketone, tertiary butyl peroxybenzoate, etc. However, it is necessary to select the most suitable organic peroxide depending on the raw material resin.

[0022] In this embodiment, the additive, polypropylene or high density polyethylene powder, has an average particle size of 10 μm to 100 μm.

[0023] For the purpose of improving the physical properties of the crosslinkable foamable composition or reducing the cost, compounding agents (fillers) that do not have a significant adverse effect on crosslinking, for example, metal oxides such as zinc oxide, titanium oxide, calcium oxide, magnesium oxide, silicon oxide, etc., carbonates such as magnesium carbonate, calcium carbonate, etc., various dyes, pigments, and fluorescent substances, other commonly used rubber and plastic compounding agents, etc., may be added as necessary.

[0024] In addition, a foaming assistant may be added according to the type of foaming agent. Specific examples of the foaming assistant include compounds containing urea as a main component, metal oxides such as zinc oxide and lead oxide, compounds containing salicylic acid, stearic acid, etc. as a main component, in other words, higher fatty acids or metal compounds of higher fatty acids.

[0025] The procedure for producing the foam in this embodiment is basically the same as that for producing conventional foams, except that polypropylene or high-density polyethylene powder is added to the polyolefin resin as the main raw material. That is, a foaming agent, a crosslinking agent, and polypropylene or high-density polyethylene powder are added to the polyolefin resin and kneaded, and then the mixture is heated to foam and obtain a foam.

[0026] The kneading process is carried out at a temperature equal to or higher than the melting point of the first polyolefin resin as the main raw material and lower than the melting point of the polypropylene or high density polyethylene as the additive, preferably at 90 to 120° C. If the temperature in the kneading process exceeds 120° C., a problem may occur in which the foaming agent or crosslinking agent reacts with the main raw material during the kneading process.

[0027] Meanwhile, the foaming process is carried out at a temperature at which the polypropylene or high density polyethylene powder can melt during the foaming process, for example, 160° C. The heating temperature during the foaming process is desirably higher than the melting point of the additive, but even if it is lower than the melting point of the additive, as long as the difference between the melting point of the additive and the heating temperature is within 10° C., the actual temperature will rise to above the melting point of the additive due to the heat generated when the foaming agent reacts with the main raw material, making it possible to melt the additive.

[0028] Table 1 shows specific examples of this embodiment. It goes without saying that the present invention is not limited to the following examples. Table 2 shows comparative examples of this embodiment.

[0029] [Table 1]

[0030] [Table 2]

[0031] Example 1: Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight of high-density polyethylene (additive) (product name: Flow Beads HE-3040, melting point 130°C, particle size 11 μm, viscosity 303.6 Pa s, manufactured by Sumitomo Seika Chemicals Co., Ltd.), 4 parts by weight of azodicarbonamide (ADCA, foaming agent), 2 parts by weight of zinc oxide (ZnO, foaming assistant), 0.5 parts by weight of zinc stearate (Zn-St, foaming assistant), and 0.6 parts by weight of dicumyl peroxide (DCP, crosslinking agent) was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes, thereby decomposing the foaming agent and crosslinking agent and foaming. The apparent density of the resulting foam was 89 kg / m 3 It became.

[0032] Example 2: Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight of polypropylene (additive) (product name: PPW-5J, melting point 143°C, particle size less than 10 μm, viscosity 0.456 Pa s, manufactured by Seishin Enterprise Co., Ltd.), 4 parts by weight of azodicarbonamide (ADCA, foaming agent), 2 parts by weight of zinc oxide (ZnO, foaming assistant), 0.5 parts by weight of zinc stearate (Zn-St, foaming assistant), and 0.6 parts by weight of dicumyl peroxide (DCP, crosslinking agent) was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes to decompose the foaming agent and crosslinking agent and foam. The apparent density of the resulting foam was 79 kg / m 3 It became.

[0033] Example 3: Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight, polypropylene (additive) (product name: Flow Beads RP-2050, melting point 146°C, particle size 10μm, viscosity 629.4 Pa s, manufactured by Sumitomo Seika Chemicals Co., Ltd.), 4 parts by weight of azodicarbonamide (ADCA, foaming agent), 2 parts by weight of zinc oxide (ZnO, foaming assistant), 0.5 parts by weight of zinc stearate (Zn-St, foaming assistant), and 0.6 parts by weight of dicumyl peroxide (DCP, crosslinking agent) was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes, thereby decomposing the foaming agent and crosslinking agent and foaming. The apparent density of the resulting foam was 88 kg / m 3 It became.

[0034] Example 4: Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight, polypropylene (additive) (product name: Toyotack H-1000P, melting point 150°C, particle size 100μm or more, viscosity 140.3 Pa s, manufactured by Toyobo Co., Ltd.), 4 parts by weight of azodicarbonamide (ADCA, foaming agent), 2 parts by weight of zinc oxide (ZnO, foaming assistant), 0.5 parts by weight of zinc stearate (Zn-St, foaming assistant), and 0.6 parts by weight of dicumyl peroxide (DCP, crosslinking agent) was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes to decompose the foaming agent and crosslinking agent and foam. The apparent density of the resulting foam was 82 kg / m 3 It became.

[0035] <Example 5> Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight, polypropylene (additive) (product name: MA04A, melting point 165°C, particle size 20μm, viscosity 813.3 Pa s, manufactured by Japan Polypropylene Corporation) 30 parts by weight, azodicarbonamide (ADCA, foaming agent) 4 parts by weight, zinc oxide (ZnO, foaming assistant) 2 parts by weight, zinc stearate (Zn-St, foaming assistant) 0.5 parts by weight, and dicumyl peroxide (DCP, crosslinking agent) 0.6 parts by weight was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes to decompose the foaming agent and crosslinking agent and foam. The apparent density of the resulting foam was 73 kg / m 3 It became.

[0036] <Example 6> Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight of polypropylene (additive) (product name: MA4AHB, melting point 165°C, particle size 20μm, viscosity 2686 Pa s, manufactured by Japan Polypropylene Corporation), 4 parts by weight of azodicarbonamide (ADCA, foaming agent), 2 parts by weight of zinc oxide (ZnO, foaming assistant), 0.5 parts by weight of zinc stearate (Zn-St, foaming assistant), and 0.6 parts by weight of dicumyl peroxide (DCP, crosslinking agent) was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes to decompose the foaming agent and crosslinking agent and foam. The apparent density of the resulting foam was 81 kg / m 3 It became.

[0037] <Comparative Example 1> Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight of ethylenediaminetetraacetate (EDTA), 4 parts by weight of azodicarbonamide (ADCA, foaming agent), 2 parts by weight of zinc oxide (ZnO, foaming assistant), 0.5 parts by weight of zinc stearate (Zn-St, foaming assistant), and 0.6 parts by weight of dicumyl peroxide (DCP, crosslinking agent) was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes, thereby decomposing the foaming agent and crosslinking agent and foaming. The apparent density of the resulting foam was 86 kg / m 3 It became.

[0038] <Comparative Example 2> Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight, PA6 (additive) (product name: A1020LP, melting point 225°C, particle size 100μm, viscosity 75.20 Pa s, manufactured by Unitika Ltd.) 30 parts by weight, azodicarbonamide (ADCA, foaming agent) 4 parts by weight, zinc oxide (ZnO, foaming assistant) 2 parts by weight, zinc stearate (Zn-St, foaming assistant) 0.5 parts by weight, and dicumyl peroxide (DCP, crosslinking agent) 0.6 parts by weight was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes, thereby decomposing the foaming agent and crosslinking agent and foaming. The apparent density of the resulting foam was 97 kg / m 3 and It became.

[0039] <Comparative Example 3> Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight, PA11 (additive) (trade name: Rilsan D30, melting point 186°C, particle size 24 μm, viscosity 316.0 Pa s, manufactured by Arkema Co., Ltd.) 30 parts by weight, azodicarbonamide (ADCA, foaming agent) 4 parts by weight, zinc oxide (ZnO, foaming assistant) 2 parts by weight, zinc stearate (Zn-St, foaming assistant) 0.5 parts by weight, and dicumyl peroxide (DCP, crosslinking agent) 0.6 parts by weight was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes to decompose the foaming agent and crosslinking agent and foam. The apparent density of the resulting foam was 108 kg / m 3 It became.

[0040] <Comparative Example 4> Ethylene-vinyl acetate copolymer (EVA, product name: Novatec EVA L V-440, melting point 89℃, density 0.938g / cm 3 (Manufactured by Japan Polyethylene Corporation)1 A composition consisting of 0.00 parts by weight of PA12 (additive) (product name: VESTOSINT 2159, melting point 184°C, particle size 10 μm, viscosity 126.0 Pa s, manufactured by Daicel-Evonik Co., Ltd.), 4 parts by weight of azodicarbonamide (ADCA, foaming agent), 2 parts by weight of zinc oxide (ZnO, foaming assistant), 0.5 parts by weight of zinc stearate (Zn-St, foaming assistant), and 0.6 parts by weight of dicumyl peroxide (DCP, crosslinking agent) was heated to 100°C and kneaded, and the kneaded mixture was filled into a mold in a press heated to 160°C and heated under pressure for 50 minutes to decompose the foaming agent and crosslinking agent and foam. The apparent density of the resulting foam was 101 kg / m 3 It became.

[0041] The above-mentioned viscosities of the resins used in the additives were measured under the conditions of 170°C and 1 Hz for high-density polyethylene and polypropylene, 240°C and 1 Hz for PA6, and 200°C and 1 Hz for PA11 and PA12.

[0042] The foam of Comparative Example 1, which does not contain any additives, shrinks in volume by 48.2% when left in a room at 100° C. for 22 hours. As described above, conventional foams made primarily from low-density polyethylene have low heat resistance and shrink significantly in a temperature environment close to the melting point of low-density polyethylene.

[0043] In contrast, the foam of Example 1, which contains high-density polyethylene powder with a melting point of 130°C, a particle size of 11 μm, and a viscosity of 303.6 Pa·s, shrinks in volume by 7.0% when left in a room at 100°C for 22 hours. The foam of Example 2, which contains polypropylene powder with a melting point of 143°C, a particle size of less than 10 μm, and a viscosity of 0.456 Pa·s, shrinks in volume by 2.5% when left in a room at 100°C for 22 hours. The foam of Example 3, which contains polypropylene powder with a melting point of 146°C, a particle size of 10 μm, and a viscosity of 629.400 Pa·s, shrinks in volume by 20.0% when left in a room at 100°C for 22 hours. Similarly, the foam of Example 4, which contains polypropylene powder with a melting point of 150°C, a particle size of more than 100 μm, and a viscosity of 140.300 Pa·s, shrinks in volume by 8.5% when left in a room at 100°C for 22 hours. The foam of Comparative Example 5, to which polypropylene powder with a melting point of 165°C, particle size of 20μm, and viscosity of 813.300 Pa s was added, contracted in volume by 17.5% when left in a room at 100°C for 22 hours. The foam of Comparative Example 6, to which polypropylene powder with a melting point of 165°C, particle size of 20μm, and viscosity of 2686.000 Pa s was added, contracted in volume by 32.8% when left in a room at 100°C for 22 hours.

[0044] Figures 1 and 2 show the polypropylene peak (2947 cm ) in the FT-IR spectrum of the mixture containing polypropylene as an additive. -1 ) strength. Figure 1 shows the results before the foaming process, and Figure 2 shows the results after the foaming process. The areas where polypropylene is present are shown as dark areas within the areas surrounded by the dashed lines at the end of the arrows in each figure. Before the foaming process, as shown in Figure 1, the aspect ratio of the polypropylene peak is close to 1:1, and polypropylene exists in a powder state. In contrast, after the foaming process, as shown in Figure 2, the aspect ratio of the polypropylene peak is significantly different, at 1:1. This shows that in the foam to which polypropylene has been added as an additive, the additive is melted and fibrillated.

[0045] Here, there is a tendency that the smaller the particle size of the resin and the lower the viscosity of the resin, the less the volume shrinks, i.e., the more excellent the heat resistance. However, when the difference in particle size and viscosity is not large, for example as in the above-mentioned Examples 3 and 5, the additive with a higher melting point melts and fibrillates during the foaming process, so that the foam using the additive with a larger particle size and viscosity may have higher heat resistance (lower heat shrinkage).

[0046] On the other hand, the foam of Comparative Example 2, to which PA6 resin powder with a melting point of 225°C and a particle size of 100μm was added, contracted by 49.7% in volume when left in a room at 100°C for 22 hours. The foam of Comparative Example 3, to which PA11 resin powder with a melting point of 186°C and a particle size of 24μm was added, contracted by 42.4% in volume when left in a room at 100°C for 22 hours. Similarly, the foam of Comparative Example 4, to which PA12 resin powder with a melting point of 184°C and a particle size of 10μm was added, contracted by 41.4% in volume when left in a room at 100°C for 22 hours.

[0047] In the above-mentioned Comparative Examples 2 to 4, unlike the Examples, the melting points of the additives are higher than the kneading temperature (160° C.) by 10° C. or more, so that the additives remain in the form of powder in the foam.

[0048] In this way, by adding polyolefin powder, which is an additive having a melting point higher than that of ethylene-vinyl acetate copolymer and meltable during the foaming process, and kneading at a temperature lower than the melting point of the polyolefin powder and then foaming, the polyolefin powder is dispersed and fibrillated during the foaming process, thereby suppressing the shrinkage of the resin skeleton of the foam and reducing the shrinkage rate in a high-temperature environment. In other words, the heat resistance of the foam can be greatly improved. Furthermore, in this embodiment, the kneading is performed at 100°C and the foaming process is performed at 160°C, so that a foam having heat resistance can be obtained by directly using equipment for producing a foam containing a conventional polyolefin resin with a low melting point.

[0049] The present invention is not limited to the above-described embodiment.

[0050] For example, not only the ethylene-vinyl acetate copolymers according to the above-mentioned Examples 1 to 4, but also any resin having a melting point of less than 120° C., such as low-density polyethylene, can be used as the main raw material of the foam according to the present invention.

[0051] Furthermore, any resin that has a melting point of 120° C. or higher, can be melted during the foaming process, and is processed into a powder form can be used as an additive for the foam according to the present invention, not limited to those used in the above-mentioned Examples 1 to 4. In this case, it is more preferable that the particle size is small and the viscosity is low.

[0052] Furthermore, the foaming step may be carried out at a temperature higher than 160° C. In this case, the heat resistance of the generated foam is not significantly different from that of the foaming step carried out at 160° C., but if the foaming step is carried out at, for example, 200° C., a resin with a melting point of about 205 to 210° C. can be used as an additive.

[0053] In addition, various modifications are possible without departing from the spirit of the present invention.

Claims

1. A step of adding a powder of an additive having an average particle size of 10 μm to 20 μm, which is formed of a resin having a melting point of 120° C. or more, to a polyolefin resin having a melting point of less than 120° C. as a main raw material, to produce a pre-foaming mixture; adding a blowing agent and a crosslinking agent to the pre-foam mixture; A step of kneading at a temperature equal to or higher than the melting point of the polyolefin resin having a melting point of less than 120° C. and lower than the melting point of the additive to disperse the powder of the additive in the pre-foaming mixture; and heating the pre-foaming mixture to a temperature at which the additive can be melted to cause foaming. A method for producing a heat-resistant crosslinked polyolefin foam comprising the steps of:

2. 2. The method for producing a heat-resistant crosslinked polyolefin foam according to claim 1, wherein the polyolefin resin is a low-density polyethylene or an ethylene-vinyl acetate copolymer.

3. 3. The method for producing a heat-resistant crosslinked polyolefin foam according to claim 1, wherein the additive is high-density polyethylene or polypropylene.

4. A heat-resistant crosslinked polyolefin foam containing a polyolefin resin having a melting point of less than 120°C as a main raw material and an additive having an average particle size of 10 μm to 20 μm formed from a resin having a melting point of 120°C or higher that has been melted and fibrillated.

Citation Information

Patent Citations

  • Manufacture of open-cell foam of polyethylene or ethylene copolymer

    JP1987064530A

  • Open-cell polyethylene resin foam and its production

    JP1990194037A

  • Open-cell foam and method for producing the same

    JP2005171064A

  • Heat-resistant crosslinked polyethylene resin foam and method for molding the same

    JP4605364B2